2019
DOI: 10.5194/wes-2019-61
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Reliability-based design optimization of offshore wind turbine support structures using analytical sensitivities and factorized uncertainty modeling

Abstract: Abstract. The need for cost effective support structure designs for offshore wind turbines has led to continued interest in the development of design optimization methods. So far, almost no studies have considered the effect of uncertainty, and hence probabilistic constraints, on the support structure design optimization problem. In this work, we present a general methodology that implements recent developments in gradient-based design optimization, in particular the use of analytical gradients, within the con… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…In other words, surrogate models mimic the behaviour of the simulation model as closely as possible while remaining computationally cheaper to evaluate. Various surrogate modelling approaches have been recently proposed in the literature for OWTs on monopile foundations, including Gaussian Process (GP) regression (8)(9)(10)(11) and for onshore wind turbines using Polynomial Chaos Expansion (12,13). These models significantly improve the computational efficiency of FLS assessment, and therefore also enable structural reliability assessment and the development of probabilistic risk models for OWTs to predict the potential financial impact of OWT failures.…”
Section: Dlcmentioning
confidence: 99%
“…In other words, surrogate models mimic the behaviour of the simulation model as closely as possible while remaining computationally cheaper to evaluate. Various surrogate modelling approaches have been recently proposed in the literature for OWTs on monopile foundations, including Gaussian Process (GP) regression (8)(9)(10)(11) and for onshore wind turbines using Polynomial Chaos Expansion (12,13). These models significantly improve the computational efficiency of FLS assessment, and therefore also enable structural reliability assessment and the development of probabilistic risk models for OWTs to predict the potential financial impact of OWT failures.…”
Section: Dlcmentioning
confidence: 99%
“…To facilitate quick assessment of computationally-expensive-to-evaluate structural responses, surrogate models have gained popularity. Authors such as [7][8][9] to mention a few, have carried out reliability-based analysis of wind turbines by employing surrogate models. Morató et al [7] carried out reliability analysis of a monopile supported wind turbine using Kriging surrogate models.…”
Section: Introductionmentioning
confidence: 99%
“…[8], only environmental uncertainties and the associated metamodel uncertainty was covered. Surrogate modeling in form of Gaussian process regression was also employed by Stieng and Muskulus [9] in the reliability-based design optimization of an offshore wind turbine (OWT) support structure. Yang et al [10] demonstrated the use Kriging model for reliability-based optimization of a tripod sub-structure.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The optimization is rarely approached using a coupled model and the definition of the optimization problem along with the optimization algorithm used is very different from research to research. Significant contributions can be found in [4]- [8]. Most works share the use of analytical sensitivities, but the treatment of the dynamic problem differs.…”
Section: Introductionmentioning
confidence: 99%